IMPLEMENTATION OF MULTICULTURAL EDUCATION AS A MEANS OF FORMING CHARACTERS OF TOLERANCE AND MUTUAL RESPECT - Arfaton, Arfaton; Yuliantri, Rhoma Dwi Aria; Lestari, Nurul Ismi; Syah, Mhd Asrian; Rizki, Iqbal Ainur; Umar, Umar (Universitas Labuhanbatu, 2025)
Purpose – Multicultural education is an important issue, especially in Indonesia, which has a diversity of cultures, religions, and ethnic groups. In education, efforts to instill tolerance and mutual respect are relevant in maintaining social harmony and preventing conflicts due to differences. This study aims to analyze the implementation of multicultural education as a means to build the character of tolerance and mutual respect among high school students.Methodology – This research uses a descriptive qualitative method. Data was collected in several senior high schools in the Wera sub-district using interview, observation, and documentation methods. Subject informants in data collection consisted of principals, teachers, and students.Findings—The results of this study show that implementing multicultural education in high schools can shape the character of tolerance and mutual respect among students. Multicultural education can be implemented in various ways, such as through group discussions, watching movies about differences in Indonesia, and using technology. Multicultural education positively influences high school students' understanding of tolerance and mutual respect for differences in the school environment and society.Significance—This research makes an important contribution to the world of education, especially in the application of multicultural education as a strategy to build tolerance and mutual respect among students. The findings can serve as a reference for educators, school principals, and educational policymakers in developing a more inclusive curriculum or learning program to instill character in students. This research can also inspire further research on innovative learning methods based on multicultural education at various levels of education. Keywords: Implementation; Multicultural Education; Characters; Tolerance; Mutual Respect